Pelvis and hind limb muscles reconstruction in the well preserved pseudosuchian Batrachotomus kupferzellensis - Lecuona, Agustina (2018)
Fil: Lecuona, Agustina. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina